Prototropic molecular-zwitterionic tautomerism of xanthine and hypoxanthine: unexpected biological view - Kondratyuk, I.V.; Samijlenko, S.P.; Kolomiets, I.M.; Potyahaylo, A.L.; Hovorun, D.M. (Биополимеры и клетка, 2000)
The prototropic molecular-zwitterionic tautomerism of xanthine and hypoxanthine has been investigated by the semi-empirical quantum-chemical AMI method. Geometric, energetic and other physico-chemical features of their complete molecular-zwitterionic families of tautomers have been established. The influence of the environment with universal solvatation mechanism on the tautomeric equilibrium has been evaluated at Otizager approximation. The comparison of the calculations with the ¹H NMR data favours the N7H Xan and the N9H Hyp tautomers in DMSO solutions. A possible biochemical role of tautomeric (especially zwitterionic) forms of Xan and Hyp is discussed. The stabilizing influences of both environment and specific interactions with proteins on rare tautomeric forms are considered. The biological significance of high energy tautomers is discussed.